Inovasi dalam memperluas jaringan UMKM: Toko bakoel plastik & pecah belah di desa gedog wetan, turen - Putri, Dinda Pandu Febriana (Maliki Interdisciplinary Journal, 2025)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in the local economy, especially during challenging times. Toko Bakoel Plastik & Pecah Belah, located in Pasar Gedog Wetan, serves as a prime example of successful innovation and adaptation. The shop owner not only sells products but also expands the business by offering new items to street vendors, thereby increasing market reach and strengthening the local community. Additionally, utilizing social media for marketing and providing online product delivery services have proven effective strategies for attracting more customers. Toko Bakoel demonstrates that with imagination and the right strategies, MSMEs can survive and even thrive amid economic challenges. This narrative emphasizes the importance of continuous innovation and openness in navigating market changes. The success story of Toko Bakoel is intended to inspire more MSME operators to adapt and innovate, thus positively impacting the local economy.